Optimization of Bauhinia monandra seed oil extraction via artificial neural network and response surface methodology: A potential biofuel candidate - Aramide M, Akintunde; Sheriff Olalekan, Ajala; Eriola, Betiku (Elsevier B.V., 2020)
Industrial Crops and Products 67 (2015) 387–394